Analisis Tingkat Stres Pada Karyawan PT Jasa Raharja Tanjungpinang - Aulia Aziva Isanti; Salma Wira Nadira; Muhammad Arif; Muhammad Zulfikar; Melisa Inggriani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores work stress among employees at PT Jasa Raharja Tanjungpinang, focusing on the impact of work demands, role expectations, organizational structure, and leadership. The research aims to provide an in-depth understanding of the factors contributing to work stress and evaluate how organizational practices influence employee well-being. Employing a qualitative approach with a descriptive method, data were gathered through interviews and observations of employees across various departments. Findings indicate that high workload, unclear role expectations, and insufficient leadership support are significant stressors. The organization’s clear structure and efficient procedures generally support task management, while leadership practices that are supportive and open contribute positively to reducing stress. Recommendations include improving workload management, setting realistic deadlines, enhancing employee training, and maintaining effective communication channels. These measures are crucial for mitigating stress, increasing employee satisfaction, and boosting productivity. The study underscores the importance of a balanced work environment, supportive leadership, and clear role definitions in managing work stress effectively.